Does Foreign Capital Increase Tax Revenue: The Turkish Case - Balıkçıoğlu, Eda; Dalgıç, Başak; Fazlıoğlu, Burcu (International Journal of Economics and Financial Issues, 2016)
We examine the effect of the foreign direct investment (FDI) on taxes paid for Turkey with a special focus on the differentials between firms operating with different technology levels. We utilize a comprehensive dataset for Turkish manufacturing firms over 2004-2012 period and employ Generalized Method of Moments methodology. The results of the study confirm that foreign affiliation increase the taxes paid by the firms. We find a bigger impact of FDI on taxation for high-technology firms than medium or low technology firms. Keywords: Foreign Direct Investment, Tax Revenue, and Generalized Method of Moments JEL Classifications: D22, F23, H2